(untitled) (Journal of Information Technology and Digital World, 2023)
Display boards have played a significant part in mass communication over the years. This work intends to propose an Internet of Things (IoT)-based online notice board. The proposed solution includes an online information flash board using IoT to decrease paperwork, time, and labour. Things are linked to the internet by IoT. As a result, the internet can be used to access the information flash board from anywhere in the world. The board has an interface for a Wi-Fi module to provide internet connectivity. The message is received from the specified user and shown on the flash board using the Wi-Fi module that is installed at the digital notice board. According to this suggested model, an authorised admin can post a message from any location, and the message will appear on the LED. The suggested concept includes several applications, such as support desks in transportation hubs including train, bus, and airport terminals that provide travellers with current/updated information. It works better, especially in congested areas like supermarkets, and decreases costs. Any remote region of the world can be represented on the screen with the most recent news, which is made possible only by IoT.